Pulmonary squamous cell carcinoma with a lepidic-pagetoid growth pattern - Guerrieri, Claudio; Lindner, Marc; Sesti, Joanna; Chakraborti, Abhishek; Hudacko, Rachel (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
We report a rare case of a peripheral squamous cell carcinoma (SCC) of the lung in which most of the tumor displayed a “lepidic” growth pattern. The tumor cells also appeared to grow along the alveolar walls between the overlying pneumocytes and underlying basement membrane, a form reminiscent of the “pagetoid” mode of spread. The neoplastic cells were positive for the squamous markers p63 and p40. TTF-1 and CK7 highlighted residual non-neoplastic pneumocytes, which either covered the lepidic tumor cells or lined pseudoglandular formations created by the filling of alveolar spaces by the tumor. CK7 also stained the tumor cells, albeit focally and weakly, a not uncommon finding in peripheral lung SCC. The tumor cells were negative for TTF-1 (clone 8G7G3/1), but did show focal weak reactivity with the less specific clone SPT24. The invasive area measured 2.5 mm while the overall size of the tumor including the lepidic-pagetoid component was 9.0 mm. Even though the invasive component was < 0.5 cm, the only option according to existing staging criteria was to stage it as pT1a. Since the current staging system does not account for the non-invasive lepidic component of pulmonary SCC, the increasing awareness of this variant may require its inclusion within the classification and pathological staging of lung carcinoma.